Antimicrobial susceptibility and minimal inhibitory concentration of Pseudomonas aeruginosa isolated from septic ocular surface disease in different animal species - Leigue, L. (Open Vet J, 2016)
The purpose of this study was to evaluate the antibiotic susceptibility profile of Pseudomonas aeruginosa isolated from different animal species with septic ocular surface disease. Sixteen strains of P. aeruginosa were isolated from different species of animals (dog, cat, horse, penguin and brown bear) with ocular surface diseases such as conjunctivitis, keratocojnuctivits sicca and ulcerative keratitis. These isolates were tested against 11 different antimicrobials agents using the Kirby-Bauer disk-diffusion method. Minimum inhibitory concentrations (MICs) were determined using E-tests for two antibiotics (tobramycin and ciprofloxacin) commonly used in veterinary ophthalmology practice. Imipenem was the most effective antibiotic, with 100% of the strains being susceptible, followed by amikacin (87.5%), gentamicin, norfloxacin, gatifloxacin and polymyxin (both with 81.5%of susceptibility). MIC(90) of ciprofloxacin was 2 µg/ml and the values found ranged from 0.094 µg/ml to 32 µg/ml. For tobramycin, MIC(90) was 32 µg/ml and ranged from 0.25 µg/ml to 256 µg/ml. The most effective in vitro antibiotic tested against P. aeruginosa in this study was imipenem, followed by amikacin. The 3 mg/ml eye drops commercially available ciprofloxacin presentations were in vitro effective against all strains tested in this study if applied up to 4 hours after instillation. Whereas for tobramycin the 3 mg/ml eye drops commercial presentations were not in vitro effective against some strains isolated in this study. Thus for ocular infections with P. aeruginosa when using tobramycin the ideal recommendation would be to either use eye drops with higher concentrations or decrease the frequency intervals from four to a minimum of every two hours.